Hegemony of Power in Literature Discourse Indonesian Language Textbook SMA - Mafrukhi Mafrukhi; Rustono Rustono; Subiyantoro Subiyantoro; Mukh. Doyin (Universitas Negeri Semarang, 2021)
The author conducts research on the hegemony of power through literary discourse in high school Indonesian language textbooks published by the Ministry of Education and Culture. Gramsci's hegemony pays attention to the process of meaning which is dominated by authoritative practices. Ideology is understood as an idea that supports a particular group. Hegemony flows downwards leading to the struggle of the oppressed against a single source of power. The purpose of this study is to analyze literary texts in high school Indonesian language textbooks that contain hegemony of power. Literary discourse in this study was analyzed in three dimensions: (1) text, (2) discourse practice, and (3) sociocultural practice. By using Fairclough's view, literary discourse in Indonesian X, XI, and XII books can be classified into hegemony of power. The discussion of literary discourse, with Fairclough's analysis, analyzes (a) the vocabulary used to represent hegemony of power, (b) the elements of literature used to represent hegemony of power, (c) the hegemony of power in literary discourse in high school Indonesian language textbooks. The hegemony of power in literary discourse is seen as having a classification of linguistic devices, types of literary elements, and hegemony of power. Literary discourse in Indonesian language textbooks is interpreted using Fairclough's critical discourse analysis to interpret the text's language, discourse practices, and social practices. The classification of vocabulary, literary elements, and power hegemony constructed by literary discourse reflects the choice of textbook authors. The implication of this research is to develop a reference for writers in choosing the right text in classroom learning.